Implementing Workplace-Based Assessments at Scale: The SIMPL Approach - Joseph B. Zwischenberger, MD; Sarah P. Hatchett; Naveed A. Rahman, MD; Priyal Chadha, BA; Stefanie S. Sebok-Syer, PhD; Brian C. George, MD, MEd (Annals of Surgery Open)
Over the past decade, medical education has shifted from a time-based approach to a competency-based approach for surgical training. This transition presents many new systemic challenges. The Society for Improving Medical Professional Learning (SIMPL) was created to respond to these challenges through coordinated collaboration across an international network of medical educators. The primary goal of the SIMPL network was to implement a workplace-based assessment and feedback platform. To date, SIMPL has developed, implemented, and sustained a platform that represents the earliest and largest effort to support workplace-based assessment at scale. The SIMPL model for collaborative improvement demonstrates a potential approach to addressing other complex systemic problems in medical education.